A link between toxocariosis and asthma: a prospective study among children at the Hospital Nacional Cayetano Heredia, Lima, Perú - Gétaz Schaller, Laurent (2024)
Introduction: the zoonotic ascarid Toxocara canis has been suggested as a possible etiologic agent of asthma. Objective: explore the association between T. canis infection and asthma in children seen at the Hospital Nacional Cayetano Heredia (HNCH), Lima, Perú, and evaluate other factors associated with T. canis infection in the population studied. Materials and methods: this is a case-control study involving 75 asthmatic and 75 nonasthmatic children, from 2 to 13 years who were evaluated at the HNCH in 2002. A questionnaire was applied referring to the interest variables. Seroprevalence of T. canis was determined through a T. canis ELISA IgG test for. Results: the seroprevalence of toxocariosis was 16 %. No significant association was found between the seropositivity for T. canis and asthma. A significant association between a higher frequency of nocturnal sibilance crises and a positive serology for T. canis. The factors associated to toxocariosis were contact with dogs, particularly with puppies, and parents without higher education (university). The factors associated to asthma were: infrequent contact with dogs and parents with a university education. Conclusions: there was no association between the presence of positive serology for T. canis and asthma, but there was an association between higher the frequency of crises of nocturnal sibilance and a positive serology for T. canis. More studies are needed to evaluate the latter observation.